SPICATIC ACID: A 4-CAROXYGENTISIC ACID FROM A GENTIANA SPICATA EXTRACT WITH POTENTIAL HEPATOPROTECTIVE ACTIVITY - Ayoub, N. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Investigation of the protective mechanisms of aqueous alcoholic extract of Gentiana spicata (Gentianaceae) in carbon tetrachloride intoxicated rats was undertaken. Rats were treated with carbon tetrachloride at the dose of 1 ml/kg body weight intraperitonially once in every 24 hrs for 14 days. The hepatoprotective activity of the extract of Gentiana spicata was evaluated by measuring levels of serum marker enzymes alanine aminotransferase (ALT) and aspartate aminotransferase (AST). Administration of the extract ( 250 mg/kg, b.wt.) significantly (p < 0.05) prevented CCl4-induced elevation of levels of serum AST and ALT. Treatment of rats with CCl4 led to a marked increase in lipid peroxidation as measured by malondialdehyde (MDA). This was associated with a significant reduction of the hepatic antioxidant system e.g. reduced glutathione (GSH). These biochemical alterations resulting from CCl4 administration were significantly (p < 0.05) inhibited by pretreatment with the extract of Gentiana spicata. These result suggest that the aqueous alcoholic extract of Gentiana spicata may act as a hepatoprotective and antioxidant agent. Phytochemical study demonstrated a high phenolic content and led to the isolation and identification of the new carboxygentisic acid, 1,4-dicarboxy 2,5-dihydroxybenzene, for which we suggest the name spicatic acid, together with the two known flavonoids, quercetin 3-O-[(2,3,4-triacetyl-a-rhamnopyranosyl)-1”’? 6”]-3-acetyl-?-galactopyranoside and quercetin 3-O-[(2,3,4-triacetyl-a-rhamnopyranosyl)-1”’? 6”]-4-acetyl-?-galactopyranoside. All structures were elucidated on the basis of conventional analytical methods and confirmed by high resolution FTMS, 1D- and 2D-NMR data. The new phenolic caroxylic acid, spicatic acid is of special interest as it represent the first phenolic acid which bears two caroxyl function in one aromatic ring elucidated on the basis of conventional analytical methods and confirmed by FTMS, 1D- and 2D-NMR data. The new compound was shown to have a slight positive effect on in vitro mineralization of SaOS-2 human osteosarcoma cells. However, it showed a significant increase of mineralized area at 20µg/mL, while at lower concentrations the effect was not of significant value. It should be noted however that an increase of the number of mineralized spots (nodules) at all concentrations tested was observed. This can be taken as an evidence for increased cell maturation and osteoblasticity. This data give rise to the notion that the compound has a contribution to the significant effect exhibited by the Feijoa sellowiana crude extract. References: 1- Hussein, S. A. M., Nawwar, M. A. M. (2006) Pharmazie 61: 2993-2996 2- Hussein, S. A. M., Nawwar, M. A. M.(2007). Phytochemistry 68: 1464-1470 Extra authors: Michael Linscheid, Vice President for research, Humboldt Universität zu Berlin, 12489 Berlin, Germany Email: michael.linscheid@cms.hu-berlin.de Manuela Harms, Institut für Pharmazie, Pharmazeutische Biologie, Ernst-Moritz-Arndt-Universität Greifswald, 17487 Greifswald, Germany Email: Harms@uni-greifswald.de Kristian Wende, Institut für Pharmazie, Pharmazeutische Biologie, Ernst-Moritz-Arndt-Universität Greifswald, 17487 Greifswald, Germany Email: wende@uni-greifswald.de Ulrike Lindequist Institut für Pharmazie, Pharmazeutische Biologie, Ernst-Moritz-Arndt-Universität Greifswald, 17487 Greifswald, Germany Email: lindequi@uni-greifswald.de Presenter: Mahmoud A. M. Nawwar Department of Phytochemistry, Division of Pharmaceutical Industries, National Research Center, Dokki, Cairo, Egypt